An innovative tool for mapping forest fire risk and danger: case studies from eastern Mediterranean. - Sağlam, Bülent; Boyatan, Mehmet; Sivrikaya, Fatih (Scottish Geographical Journal)
Forest fires are one of the most important factors for forest ecosystem and cause ecosystem destruction such as decreasing forest area, biodiversity in the Mediterranean region. Türkiye located in Mediterranean region is exposed to hundreds of fires every year, which damage forest. Mapping forest fire risk and danger constitutes an important basis for preventing fire damages. Geographical Information System is used for mapping forest fire risk and making the accurate and fast decision. This study is designed to develop a GIS-based decision support systems (DSS) to produce a forest fire risk and danger map for Türkiye. DSS uses topography, stand structure and anthropogenic factors for mapping forest fire risk and danger. DSS was developed using the C-sharp (C#) programming language with the help of Add-in in the ArcGIS. DSS has been successfully tested on case study sites in Kozan and Milas Forest Enterprises in Türkiye. In conclusion, the DSS has contributed to the forest managers to fight forest fire effectively. This study will make an important contribution to both the General Directorate of Forestry, which is in the position of implementing it, and the scientific community.